Kompetensi Interpersonal Mahasiswa - Muhammad Idrus (Universitas Islam Indonesia, 2009)
This research proposes to evaluate a correlation between same-aged friendship interactionand inter-personal competence of students. The population are all students of theFaculty of Psychology and Social and Cultural Science of the Universitas Islam Indonesia.Samples are 25 percent of the population, 315 students, taken through the stratified proportionalrandom. Using a product moment correlation analysis of Pearson, it is revealedthat the value of the correlation between the same-aged interaction and inter-personalcompetence is 0.457 (p=0.000). This shows a significant correlation between these variables.Keywords: same-age friendship, interpersonal competence, correlation.